Analisis Kualitas Udara Ruangan di Ruang Rawat Inap Rumah Sakit - Nur Nazliyatun Nada; Vivi Filia Elvira; Sahrinai (Buletin Keslingmas, 2026)
Hospitals are environments that have the potential to experience indoor air pollution. RSUD X Samarinda is a type C hospital in Samarinda that provides emergency, outpatient, and inpatient services. The inpatient room is a place for patients who are recovering and is often a place of interaction between patients, medical staff, non-medical staff, and visitors. Thus, sanitation in the treatment room is important to note. The method used is the quantitative method with a descriptive design. The measurement results show that the temperature and humidity in all inpatient rooms have abnormal temperature, pressure, and humidity levels. The measurement results of PM2.5 concentration in accordance with the standard in TB isolation room 1 amounted to 0.25 µg/m3, and isolation room/HCU with a concentration of 0.24 µg/m3. And the results of measuring PM10 concentrations in inpatient rooms are all in accordance with hospital environmental health quality standards. The quality standard used is the Regulation of the Minister of Health of the Republic of Indonesia Number 2 of 2023 concerning the Implementation Regulation of Government Regulation Number 66 of 2014 concerning Environmental Health. have a large proportion to highlight the interest of your research.